2018
DOI: 10.1007/s00421-018-3841-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in kinematics and energy cost between front crawl and backstroke below the anaerobic threshold

Abstract: Front crawl is less costly than backstroke, and limbs motion in front crawl is more effective than in backstroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 42 publications
1
30
5
2
Order By: Relevance
“…The above-referenced comparisons between swimming techniques were made possible since v AnT occurred at ~92 % of the velocity of the last protocol step in all four of them, a similar value to that found in the literature [33,34]. However, [La] AnT assessment were not reliable when analysing swimming techniques between upper and lower limb-action groups, since a [La] AnT lower than 3.5 mmol • l − 1 corresponded to a higher velocity than v3.5, confirming the assertion that swimming techniques are not equal biophysical terms [4,18,31]. Moreover, we observed that front crawl presented higher velocities in all five steps of the incremental protocol.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The above-referenced comparisons between swimming techniques were made possible since v AnT occurred at ~92 % of the velocity of the last protocol step in all four of them, a similar value to that found in the literature [33,34]. However, [La] AnT assessment were not reliable when analysing swimming techniques between upper and lower limb-action groups, since a [La] AnT lower than 3.5 mmol • l − 1 corresponded to a higher velocity than v3.5, confirming the assertion that swimming techniques are not equal biophysical terms [4,18,31]. Moreover, we observed that front crawl presented higher velocities in all five steps of the incremental protocol.…”
Section: Discussionsupporting
confidence: 84%
“…Each swimmer's anaerobic profile was established with two derived indicators: (i) the blood lactate increase rate ([La] rate; adapted from [21]), as the ratio between the net [La] and velocities (Δ [La] and Δv, respectively) of the two last protocol steps; and (ii) the blood lactate increase speed (BLIS) of 4 th and 5 th steps, as the time rate of net [La] per step (difference between the [La] obtained after the current step and the previous one, and the time needed to accomplish the 200 m step; adapted from [1]). Swimming techniques were analysed individually and by alternated (front crawl and backstroke) and simultaneous (breaststroke and butterfly) upper and lower limb-action groups, given the obvious dichotomy between them [4,18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomechanical asymmetries are useful both for clinical and research purposes, permitting the characterization of the functional imbalances between contralateral limbs [31]. Theoretically, the front crawl and backstroke intracycle velocity variation can be enhanced by this functional imbalance, increasing the energy cost of swimming [32,33] and deteriorating body postures with increasing hydrodynamic drag [10] at a given swimming speed. The current results demonstrate that elite swimmers are more symmetrical than lower level swimmers (data from [16]), since we did not observe considerable differences between the force production of contralateral body sides.…”
mentioning
confidence: 99%
“…In the present study, LED lights on the device are separated by 1 m and the lights flash intermittently. Even though this type of the pacer (with flashing lights have 1 m or more distance between them) has been widely used in swimming research (Aspenes et al, 2009;Figueiredo, Barbosa, Vilas-Boas, & Fernandes, 2012;Gonjo et al, 2018;Kjendlie, Ingjer, Madsen, Stallman, & Stray-Gundersen, 2004;Marinho et al, 2004), intermittent flashing means that swimmers are not informed of the required speed constantly by the system.…”
Section: Discussionmentioning
confidence: 99%